Determinants of the exchange rate in Egypt and their implications for economic development econometrics study during the period (1971-2018) - Abudeif, Salwa Mahmoud; Ali, Sammer Hussein (Journal of Economic, Administrative and Legal Sciences, 2021)
The current study aims to analyze the components and determinants of the exchange rate in Egypt and to clarify its implications for economic development. By using the descriptive and analytical approaches and the econometrics and quantitative approaches, which consists of a dual model, in the first part, the determinants of the exchange rate and their effects on the exchange rate in Egypt are evaluated, and then the second part deals with the study of the relationship between the exchange rate and economic development (measured by GDP) in Egypt through The use of Johansson’s method of co-integration and the use of time series data for model variables for a period of about 47 years, which starts from 1971 to 2018.The study found results, the most important of which is for the exchange rate model that there is an inverse relationship between inflation and the exchange rate, and there is a direct relationship between the interest rate and the exchange rate. As for the economic development model, there is a direct relationship between commodity imports and the rate of economic growth and an inverse relationship between the exchange rate and the rate Economic growth.